The first record of the Nearctic genus Kearfottia Fernald, 1904 (Lepidoptera, Psychidae) from the Palaearctic Region (Japan) - Saigusa, Toyohei; Sugimoto, Mika (Zootaxa, 2021)
Kearfottia japonica Saigusa & Sugimoto, sp. nov. (Lepidoptera, Psychidae) is described from Japan. This species is the second species of the genus Kearfottia hitherto known only from one Nearctic species, K. albifasciella Fernald, 1904. Bionomics of the Japanese species, systematic position and zoogeography of the genus are discussed.